Semiconductor Nanowires. - Dayeh, Shadi A.; Fontcuberta i Morral, Anna; Jagadish, C. (Chennupati) (Semiconductors and semimetals, 2016)
Semiconductor Nanowires: Part B, and Volume 94 in the Semiconductor and Semimetals series, focuses on semiconductor nanowires. This book will be of interest to scientists and engineers performing fundamental and applied research and technology development in the field of one-dimensional nanowires. The book will particularly appeal to physicists, chemists, materials scientists, electronics engineers and mechanical engineers. This book will be of interest to students, researchers and practitioners working in the field of semiconductors, mechanical, electronic and optoelectronic devices.